2017
DOI: 10.1002/chem.201704661
|View full text |Cite
|
Sign up to set email alerts
|

Readily Exfoliated TiSe2 Nanosheets for High‐Performance Sodium Storage

Abstract: Materials with sheet-like morphologies are highly desirable candidates for energy storage and conversion applications, due to the confined atomic thickness and high surface area, which would largely improve the electrochemical reaction kinetics. In this work, the sodium storage performance of TiSe nanosheets and corresponding sodiation/desodiation reaction mechanism are studied for the first time. TiSe nanosheets are readily exfoliated from bulk TiSe after quick ultrasonication or grinding. The TiSe nanosheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 44 publications
0
24
0
2
Order By: Relevance
“…[ 23,25,30,31 ] In SIBs system, four oxidation peaks can be noticed in the first cycle at around 2.02, 2.08, 2.25, and 2.35 V, which represent Na‐extraction from the VS 2 host, while only two broad peaks are located at 1.96 and 1.56 V during the reduction process, corresponding to Na + insertion into the VS 2 cathode (Figure 2b). [ 26,32,33 ] In PIBs system, three cathodic peaks attributed to K + insertion are located at 2.20, 2.11, and 1.73 V, while three anodic peaks assigned to K + extraction are situated at 1.94, 2.32, and 2.91 V in the initial cycle (Figure 2c). [ 34 ] The discharge/charge curves of the VS 2 cathode consist of two discharge plateaus at 2.31 and 2.20 V, and four charge plateaus at around 2.23, 2.32, 2.41, and 2.48 V in LIBs (Figure 2d); two pairs of redox voltage plateaus at 2.11/1.63 and 2.30/1.90 V in SIBs (Figure 2e); two discharge voltage plateaus located at around 2.21 and 1.78 V and four charge voltage plateaus located at about 1.91, 2.47, 2.90, and 3.29 V in PIBs (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23,25,30,31 ] In SIBs system, four oxidation peaks can be noticed in the first cycle at around 2.02, 2.08, 2.25, and 2.35 V, which represent Na‐extraction from the VS 2 host, while only two broad peaks are located at 1.96 and 1.56 V during the reduction process, corresponding to Na + insertion into the VS 2 cathode (Figure 2b). [ 26,32,33 ] In PIBs system, three cathodic peaks attributed to K + insertion are located at 2.20, 2.11, and 1.73 V, while three anodic peaks assigned to K + extraction are situated at 1.94, 2.32, and 2.91 V in the initial cycle (Figure 2c). [ 34 ] The discharge/charge curves of the VS 2 cathode consist of two discharge plateaus at 2.31 and 2.20 V, and four charge plateaus at around 2.23, 2.32, 2.41, and 2.48 V in LIBs (Figure 2d); two pairs of redox voltage plateaus at 2.11/1.63 and 2.30/1.90 V in SIBs (Figure 2e); two discharge voltage plateaus located at around 2.21 and 1.78 V and four charge voltage plateaus located at about 1.91, 2.47, 2.90, and 3.29 V in PIBs (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TiSe 2 is expected to have fast intercalation and deintercalation of alkali metal cations due to the larger interlayer spacing (0.601 nm) and better electronic conductivity compared with that of TiS 2 (0.569 nm). Zhang et al reported high‐performance SIBs based on TiSe 2 nanosheets via an exfoliation method. The TiSe 2 nanosheets exhibited a reversible capacity of 147 mAh g −1 with 0.1 A g −1 and showed an excellent rate capability (10 3 mAh g −1 ) at an ultrahigh current density of 10.0 A g −1 .…”
Section: Device Applicationsmentioning
confidence: 99%
“…Zhang 等 [30] 9) 图 3 (a) SnSe2/rGO 嵌钠过程结构演变示意图 [33] ; (b) SnSe/C 在不同电压下测试获得的非原位 XRD 曲线 [35] Figure 3 (a) Schematic diagram of the structure evolution of SnSe2/rGO during the insertion process [33] ; (b) Ex-situ XRD of SnSe/C under different voltages [35] 然而,SnSe 电极在循环过程中容易产生较大的 体积膨胀, 由此导致较弱的循环稳定性以及动力学问 题。目前,通常通过结构构建以及与其他材料复合等 方法进行改善。在结构构造方面,SnSe 纳米片最为 常见,层状结构的 2D 电极材料在钠离子电池中具有 巨大的应用潜力,Wang 等 [36] 利用新型胶体化学法, 制备了 2D 超薄层状的 SnSe 纳米片,这种独特的结 构可以实现钠离子电池中快速的离子及电子的传输, 在 50 mA g -1 的电流密度下能够保持 463 mAh g -1 的容 量。Yuan 等 [37] [44] [41] ; (c) TiSe2 的原位 XRD 测试 [44] 。 Figure 4 (a) Ex-situ XRD and (b) Ex-situ Raman test of WSe2 nanosheets [41] ; (c) In-situ XRD test of TiSe2 during the first two charge and discharge processes [44] .…”
Section: 引言unclassified